(untitled) (Publicacions de la Universitat de València, 2019)
This study examines the fiction of contemporary American author George Saunders in terms of how it presents situations applicable to the chief notions of posthumanist ethics and how these conceptions concern nonhuman animals, which are prevalent in his writing. Posthumanist ethics can help us understand what is at play in Saunders’s fiction. Meanwhile, his texts can help us understand what is at stake in posthumanist ethics. This interdisciplinary project may be beneficial both to conceiving new notions of ethics that are more inclusive and, more implicitly, to understanding the relevance of Saunders’s fiction to the current American sociocultural climate. Aquest estudi examina la ficció de l’autor estatunidenc contemporani George Saunders: com presenta situacions aplicables a les principals nocions de l’ètica posthumanista i com aquestes concepcions concerneixen els animals no humans, que prevalen en els seus escrits. L’ètica posthumanista pot ajudar-nos a entendre el que està en joc en la ficció de Saunders, mentre que els seus textos poden ajudar-nos a entendre el que està en joc en l’ètica posthumanista. Aquest projecte interdisciplinari pot ser beneficiós tant per a concebre noves nocions d’ètica que siguen més inclusives com, més implícitament, per a comprendre la rellevància de la ficció de Saunders en l’actual clima sociocultural estatunidenc.